2023
DOI: 10.3390/plants12112187
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Seed Priming under Salt Stress Conditions on Physiological, and Biochemical Attributes of Micro-Tom Tomato Plants

Abstract: Pre-sowing seed priming is one of the methods used to improve the performance of tomato plants under salt stress, but its effect photosynthesis, yield, and quality have not yet been well investigated. This experiment aimed to alleviate the impact of sodium chloride stress on the photosynthesis parameters of tomato cv. Micro−Tom (a dwarf Solanum lycopersicum L.) plants exposed to salt stress conditions. Each treatment combination consisted of five different sodium chloride concentrations (0 mM, 50 mM, 100 mM, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…One of the key advantages of seed priming is its ability to enhance osmolyte accumulation within plant cells. Osmolytes such as proline, glycine betaine, and soluble sugars are like cellular superheroes, helping plants maintain water balance and structural integrity during stressful conditions like salinity [3,25]. When seeds are primed, they kickstart the production of these crucial compounds, essentially equipping plants with a built-in defense mechanism against water scarcity and osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the key advantages of seed priming is its ability to enhance osmolyte accumulation within plant cells. Osmolytes such as proline, glycine betaine, and soluble sugars are like cellular superheroes, helping plants maintain water balance and structural integrity during stressful conditions like salinity [3,25]. When seeds are primed, they kickstart the production of these crucial compounds, essentially equipping plants with a built-in defense mechanism against water scarcity and osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of the seed priming reagents were determined based on previous research findings. The concentration of PEG6000 was selected according to the study by Habibi et al [3], while for NaCl, Nakaune et al demonstrated that a concentration of 300 mM can enhance seedling vigor and other characteristics in tomatoes [18]. However, for a combined treatment of seed priming reagents, 300 mM NaCl was a high dose.…”
Section: Cultivation and Application Of Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations